“Waiting for DAAs”: A retrospective chart review of patients with untreated hepatitis C in Rwanda - Gupta, N; Kabahizi, J; Mukabatsinda, C; Walker, T; Musabeyezu, E; Kiromera, A; Van Nuil, J; Steiner, K; Mukherjee, J; Nsanzimana, S; Mbituyumuremyi, A (Public Library of Science, 2017)
Background Access to treatment for hepatitis C virus (HCV) in sub-Saharan Africa is extremely limited. With the advent of direct acting antivirals (DAAs), highly effective and easy-to-deliver oral regimens are now available on the global market. This study was conducted to understand the background and characteristics of a national cohort of patients with HCV infection enrolled in care and awaiting therapy with DAAs. Methods and findings We conducted a retrospective chart review of all adult patients with confirmed HCV infection who were currently enrolled in care and treatment at the four existing hepatitis referral centers in Rwanda. Patient charts at these centers were reviewed, and routinely collected data were recorded and analyzed. Overall, 253 patients were identified; median age was 56 years (IQR: 43, 65), and 149 (58.9%) were female. Median viral load was 688,736 IU/ml and 96.7% were HCV genotype 4. As classified by FIB-4 score, 64.8% of the patients had moderate to severe fibrosis. Fibrosis stage was associated with age (OR 1.12, CI 1.09–1.17), but not with time since diagnosis, gender, treatment center, or type of insurance. There was a low frequency of documented co-morbid conditions, including hypertension, diabetes, HIV, and hepatitis B virus. Conclusions Compared to an estimated 55,000 patients eligible for HCV treatment in Rwanda, this study identified only 253 patients currently diagnosed and engaged in care, highlighting an immense treatment gap in HCV, likely due to the lack of accessible and affordable screening, diagnostic, and treatment modalities. The patients that were enrolled in care had a disproportionately advanced fibrosis stage, possibly indicating late presentation to care or lack of treatment options. In the context of newly available and effective treatment options, this study supports the overall need to accelerate access to HCV screening, diagnostics, and care and treatment services in resource-limited settings in sub-Saharan Africa.